Teaching music history with cases : a teacher's guide - Haefeli, Sara (New York, NY : Routledge, 2023)
"Teaching Music History with Cases introduces a pedagogical approach to music history instruction in university coursework. What constitutes a music-historical "case?" How do we use them in the classroom? In business and the hard sciences, cases are problems that need solutions. In a field like music history, a case is not always a problem, but often an exploration of a context or concept that inspires deep inquiry. Such cases are narratives of rich, complex moments in music history that inspire questions of similar or related moments. This book guides instructors through the process of designing a curriculum based on case studies, finding and writing case studies, and guiding class discussions of cases"--
Case study curriculum design -- Selecting and writing cases -- Class discussion -- Student inquiry and project-based learning -- Assessment in the case study classroom -- Appendix 1 : Sample course schedules -- Appendix 2 : Sources for case study materials -- Appendix 3 : Sample case study narrative : The 1589 musical inventory of the Mexico cathedral -- Appendix 4 : Research questions in published scholarship.
Keywords: Music -- History and criticism -- Study and teaching (Higher); Critical pedagogy; MUSIC / Instruction & Study / Appreciation; MUSIC / Instruction & Study / General